IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM MEMBENTUK KECAKAPAN SPIRITUAL SISWA KELAS V SD NEGERI 163080 DAN SD NEGERI 163084 KOTA TEBINGTINGGI - . hanifah (JURNAL TEMATIK, 2017)
The research aims to (1) describe how the implementation of the scientific approach in shaping the students spiritual skills for V grade student in primary schools 163080 and 163084 Town Tebingtinggi, (2) describe what the factors supporting and inhibiting the implementation of scientific approach in shaping the spiritual skills fifth grade students in primary schools 163080 and 163084 Town Tebingtinggi. Subjects in this study is teachers and 30 students of the fifth grade in primary schools 163080, teachers and 31 students of the fifih grade in primary schools163084 Town Tebingtinggi. The results showed that in theory teachers already know about the scientific approach, but in practice the teacher is not optimal, from observing the process until the end of learning. Spiritual skills of students in two primary schools Town Tebingtinggi obtained who had achieved quite well for V grade student at two primary schools in the district Town Tebingtinggi showed that of 27 aspects of spiritual skills observed oly 15 aspects that can be implemented quite well. But 12 more aspect can not be done well enough. Thus the implementation of the scientific approach in shaping the students spiritual skills in two primary schools in the district Town Tebingtinggi can be achieved quite well. But it still need improvement in some indicators that have not been achieved by students.